MORFOLOGI STRUKTUR DAN KARAKTERISTIK SIFAT MEKANIK SERTA KEAUSAN BAJA BAINIT DENGAN VARIASI MANGAN HASIL NORMALISING UNTUK TAPAK KENDARAAN TEMPUR [Morphology The Structure And Mechanical Properties And Wear of Normalizing Bainitic Steel With Various Manganese For Track Link of Combat Vehicle] - Pratomo, Sri Bimo (Jurnal Metalurgi, 2015)
Imported track link for combat vehicle uses bainitic steel. Bainitic steels are widely used because they exhibit hard but tough. To improve the mechanical properties of casting product generally are performed normalizing heat treatment. The final stage of normalizing namely cooling process greatly affects the change of microstructure morphology. Effect of manganese in the formation of bainitic structure is still debated. The purpose of this study was observing effect the manganese content and effect the various cooling process of bainitic steel track link on microstructures, hardness and abrasive resistant. Due to the formation of massive bainitic ferrite, the hardness and abrasive resistance of track link prototype containing 2% manganese becomes higher compared with track link prototype contains only 1% manganese. The track link prototype containing 1% manganese and normalized by the cooling fan, produced the microstructure of compact bainitic ferrite that has hardness and abrasive resistance was. better compared to imported track link; ie 31 HRC, 0.28% and 28 HRC, 0.52%, respectively for the track link prototype and imported track link. Compact bainitic ferrite microstructure showed better morphology compared to the massive bainitic ferrite microstructure.